GENRE CHARACTERISTICS OF ADVERTISING TEXTS - Murotov, Hamro (Журнал иностранных языков и лингвистики, 2023)
The article is devoted to the genre characteristics of advertising texts, in which problems related to the essence, scientific significance and a number of genre characteristics of advertising texts are studied and expressed.